(untitled) - Tamadachi, Michugo (Neptune City, NJ (One T.F.H. Plaza, Neptune City, 07753), 1990)
The book is an excellent reference for beginners and experts as well. It gives a great overview of the history of Japanese, Domestic and German Koi. It gives an excellent review of the different types of Koi that have help me a great deal in identification.
Keywords: Koi,Fisheries